Response to Comment on "Mechanism of PtIV Sonochemical Reduction in Formic Acid Media and Pure Water". Issue 50 (11th November 2013) - Chave, Tony; Nikitenko, Sergey I.
<x xml:space="preserve">Abstract</x> Contrary to radiolysis, sonochemistry is not only based on radical processes and further effects such as local activation or heating must be considered in particular for the sonolysis of formic acid. In the same way, the high local concentration of radicals observed in sonochemistry can induce different mechanisms compared to radiolysis.